Faecalibacterium prausnitzii Colonization Attenuates Gut Inflammation and Epithelial Damage in a DSS-Induced Colitis Mice Model - Meng-Chuan Liu; Yu-An Shu; Yu-Chin Wang; Hsiu-Ying Tseng; Meng-Jia Li; Yu-Ting Yu; Hsiu-Chi Cheng; Pei-Jane Tsai; Yao-Jong Yang (Mediators of Inflammation)
Conclusion: We have successfully established a mouse model colonized with F. prausnitzii via rectal enema administration and showed colonization of F. prausnitzii in the gut has a protective effect against DSS-induced colitis.